2015
DOI: 10.1111/dar.12295
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol outlet density and violence: A geographically weighted regression approach

Abstract: The relationships between outlet density and violence vary significantly across space for off-licences and restaurants/cafés. These results suggest that in order to minimise alcohol-related harms, such as violence, locally specific policy interventions are likely to be necessary. [Cameron MP, Cochrane W, Gordon C, Livingston M. Alcohol outlet density and violence: A geographically weighted regression approach. Drug Alcohol Rev 2016;35:280-288].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 31 publications
3
42
0
2
Order By: Relevance
“…Between our off premises counts and on-premises patron capacity, we calculated an insignificant (p > 0.05), and low correlation (<0.30 correlation coefficient). These results show that congruent with other studies, our GLM model showed that bars and pubs have a greater factor increase on assault and disorder crime compared to off-premises licenses or other on-premises establishments [2,3,22,23,40,[42][43][44][45]. The locations of bars and pubs within DAs, and in neighboring DAs units (lag), had a significant association with (p < 0.05) assault and disorder crime counts.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Between our off premises counts and on-premises patron capacity, we calculated an insignificant (p > 0.05), and low correlation (<0.30 correlation coefficient). These results show that congruent with other studies, our GLM model showed that bars and pubs have a greater factor increase on assault and disorder crime compared to off-premises licenses or other on-premises establishments [2,3,22,23,40,[42][43][44][45]. The locations of bars and pubs within DAs, and in neighboring DAs units (lag), had a significant association with (p < 0.05) assault and disorder crime counts.…”
Section: Discussionsupporting
confidence: 90%
“…These limitations make it hard to distinguish individual establishment effects [31][32][33][34][35][36][37][38][39]. Other studies separate establishment types (on verses off premises), but do not differentiate between establishment size [2,3,22,23,[40][41][42][43][44][45]. One study represents on-premises alcohol licenses by size (patron seats), but uses a hypothetical change in alcohol establishment locations to indicate rises in crime [46].…”
Section: Introductionmentioning
confidence: 99%
“…These relationships depend on a variety of factors, such as individual drinking patterns and preferences, and social and structural characteristics such as access to transport. 20 75 Where conditions are more uncertain, researchers have applied alternative models of foraging behavior. 21,22 If resources are randomly available and access is influenced by a multiplicity of factors, foraging would likely involve a more random search pattern.…”
Section: Random Brownian Motionmentioning
confidence: 99%
“…By definition, with off-licence venues the location of alcohol purchase differs from the location of consumption. For on-licenced venues there is no separation between the location of purchase and consumption meaning that any alcohol-related violence is more likely to occur within a small vicinity of the venue (Cameron et al 2016). Secondly, by focusing upon taverns, we ensure that we consider only venues where the consumption of alcohol can be considered to be the main activity undertaken.…”
Section: Location Of Tavernsmentioning
confidence: 99%
“…Within the New Zealand context, where it has been estimated that approximately 31% of all recorded crime is perpetrated by an individual who has consumed alcohol prior to offending (Stevenson 2009), there is an extremely well developed body of literature linking alcohol outlet density and violent crime (Cameron et al 2012(Cameron et al , 2016. Furthermore, there is also a growing body of evidence linking alcohol outlet proximity to instances of violence.…”
Section: Introductionmentioning
confidence: 99%